2023
DOI: 10.3389/fpls.2023.1044581
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptomics and metabolomics analysis provide insight into anthocyanin biosynthesis for sepal color formation in Heptacodium miconioides

Abstract: Heptacodium miconioides Rehd., commonly known as “seven-son flower,” is an ornamental species with a beautiful flower pattern and persistent sepals. Its sepals are of horticultural value, turning bright red and elongating in the autumn; however, the molecular mechanisms that cause sepal color change remain unclear. We analyzed the dynamic changes in anthocyanin composition in the sepal of H. miconioides at four developmental stages (S1-S4). A total of 41 anthocyanins were detected and classified into 7 major a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Usually, the sepals exhibit green colors because of the chlorophyll accumulation, while petals show a wider range of colors caused by the synthesis of abundant secondary metabolites, including flavonoids, carotenoids and betaines. However, the sepals of a few plants possess the ability to accumulate anthocyanins instead of chlorophylls, such as delphinidins in H. macrophylla [31,32], and cyanidins and pelargonidins in Heptacodium miconioides [33]. In this study, the anthocyanins in the red sepals of F. hybrida were mainly cyanidin and peonidin derivatives, different from the malvidin derivatives accumulating in its purple petals (Figure 2, Table S3).…”
Section: Discussionmentioning
confidence: 60%
“…Usually, the sepals exhibit green colors because of the chlorophyll accumulation, while petals show a wider range of colors caused by the synthesis of abundant secondary metabolites, including flavonoids, carotenoids and betaines. However, the sepals of a few plants possess the ability to accumulate anthocyanins instead of chlorophylls, such as delphinidins in H. macrophylla [31,32], and cyanidins and pelargonidins in Heptacodium miconioides [33]. In this study, the anthocyanins in the red sepals of F. hybrida were mainly cyanidin and peonidin derivatives, different from the malvidin derivatives accumulating in its purple petals (Figure 2, Table S3).…”
Section: Discussionmentioning
confidence: 60%
“…The identified metabolites, such as flavonoids, soluble sugars, and lignin, including galactose, manninotriose, glucose, luteolin, and coniferin, were found to play important roles in 1-year-old peach branches in response to cold. The findings concluded that the galactose metabolism, phenylpropanoid biosynthesis, and flavonoids biosynthesis pathways were associated with the low temperature tolerance of peaches (Li et al, 2023).…”
Section: Metabolomics In Spring Frost Studymentioning
confidence: 92%
“…In particular, the most abundant sRNAs were 24 nt, followed by 21 nt and 22 nt in all three varieties. The rRNAs (853,418-1,354,362), snoRNA (25,637), snRNA (1,494-3,088), sRNA (17,859), and tRNA (3,346) were annotated through searching against GenBank, tRNAdb, Rfam, Repbase, and Silva databases (Table 5).…”
Section: Analysis Of Differentially Expressed Mrnas Between Three Var...mentioning
confidence: 99%
“…Flower color, important objective in ornamental plant breeding, are controled by integrated effects of pigment composition, pH, cell shape, and copigmentation (Sinopoli et al 2019; Wang et al 2023;Li et al 2023). Several hundred genes associated with ower color formation, containing transcription factors, transcriptional co-regulators, proteins involved in epigenetic control of gene expression, and microRNAs, have been well identi ed in model plant (Selva et al 2021; Guan et al 2021;Ren et al 2021;Takeda et al 2023).…”
Section: Introductionmentioning
confidence: 99%